Are Female Undergraduates at the University of Calabar Equipped with the Knowledge, Positive Attitudes, and Effective Practices of Contraceptives? - Etuk, Emediong Saturday; Daniel, Faithful Miebaka; Gbuchie , Monica Anurika; Eyo, Akwa Archibong; Emeruwa, Victoria Ezinne (International Journal of Medical Students, 2023)
BACKGROUND: The global challenge of rapid population growth necessitates family planning programs to address reproductive health needs and control population increase. However, unintended pregnancies, particularly among adolescents, remain a significant problem, leading to increased risks of sexually transmitted infections and unsafe abortions. In Nigeria, contraceptive use is low among youths, resulting in high incidences of induced abortions and sexually transmitted infections. Barriers such as religious beliefs, cultural factors, limited availability, personal beliefs, and fear of side effects contribute to the under-utilization of contraceptives. METHODS: A descriptive cross-sectional study was conducted among female undergraduates of the University of Calabar, Cross River State. Data was collected using a 42-item questionnaire after obtaining informed consent. Multi-stage sampling was employed, and data was analyzed with IBM SPSS version 26 using descriptive and inferential statistics. RESULTS: The mean age of respondents was 21.5 ± 2.72 years. Most participants were in their first (26.7%) or second (22.6%) level of study. 28.8% were in sexual relationships, while 71.2% were not. Approximately a quarter of respondents had experienced symptoms of sexually transmitted infections. 71.5% had no knowledge of emergency contraception. Condoms (71.2%) and pills (54.5%) were the most commonly mentioned methods of contraception, while tubal ligation was the least popular (4.7%). The main benefit cited for contraception was the prevention of unwanted pregnancy (92.2%). 47.3% had no idea about the side effects of contraception, with irregular menstruation being the most commonly mentioned side effect (19.3%). Friends/peers, the internet, and school were the primary sources of information on contraception. 56.4% believed that contraception is not solely for females and should not be reserved for the literate. Over a third of respondents thought contraception encourages promiscuity and has too many side effects, with more than half demanding contraceptive services on campus. Less than half of the respondents (43.9%) reported using contraception at some point, with even smaller percentages using contraception in the last six months (25.2%) or during their last sexual intercourse (23.8%). Of the 101 who used contraceptives in their last sexual intercourse, the majority (83%) used condoms, while pills (7%) and emergency contraception (10%) were less common. Preferred sources for contraception were pharmacies (57.5%) and chemist shops/patent medicine vendors (24.7%). Religion (41.5%), fear of side effects (34.9%), and partner consent (28.3%) were the main influences on contraceptive use. Several factors were significantly associated with contraception utilization, including age, partner’s educational level, knowledge of contraception, and level of study (p<0.05). CONCLUSION: The low utilization of contraception among female undergraduates at the University of Calabar despite high awareness and poor knowledge highlights the need for interventions. Factors influencing utilization include age, knowledge, and level of study. Barriers such as religion, fear of side effects, and partner consent must be addressed. Recommendations include sensitization campaigns, establishing a youth-friendly center on campus, incorporating contraception into curricula, collaborating with NGOs, and increasing funding for research.